2009
DOI: 10.1007/s11240-009-9500-7
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration in date palm Phœnix dactylifera L., cv. Boufeggous is significantly improved by fine chopping and partial desiccation of embryogenic callus

Abstract: Plant regeneration through somatic embryogenesis from young leaf explants (5-10 mm long) adjacent to the apex of 5-6 year old offshoots of Tunisian date palm (Phoenix dactylifera L.), cultivar Boufeggous was successfully achieved. Factors affecting embryogenic callus initiation, including plant growth regulators and explant size, were investigated. The highest induction frequencies of embryogenic calli occurred after 6-7 months on MS medium supplemented with 10 mg l -1 2,4-D and 0.3 mg l -1 activated charcoal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
10

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 41 publications
8
53
0
10
Order By: Relevance
“…The presence of the hydrolytic enzyme "invertase" in plant cell wall and vacuole that breaks down sucrose into glucose and fructose for plant metabolism may be responsible for the superiority of sucrose over other carbon sources (Arnd and Guo-Qing, 1999). The superiority of sucrose over the other sugars employed as carbon source in this study is consistent with earlier reports for other plants such as Phoenix dactylifera (Veramendi and Navarro, 1996;Othmani et al, 2009) used as a sole carbon source and Dianthus caryophyllus (Karami et al, 2006). Baskaran and Jayabalan (2005) suggested that among the three carbon sources, sucrose proved to be better than fructose or glucose for shoot regeneration of Eclipta alba.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of the hydrolytic enzyme "invertase" in plant cell wall and vacuole that breaks down sucrose into glucose and fructose for plant metabolism may be responsible for the superiority of sucrose over other carbon sources (Arnd and Guo-Qing, 1999). The superiority of sucrose over the other sugars employed as carbon source in this study is consistent with earlier reports for other plants such as Phoenix dactylifera (Veramendi and Navarro, 1996;Othmani et al, 2009) used as a sole carbon source and Dianthus caryophyllus (Karami et al, 2006). Baskaran and Jayabalan (2005) suggested that among the three carbon sources, sucrose proved to be better than fructose or glucose for shoot regeneration of Eclipta alba.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, such explants are not appropriate for true-to-type propagation [18]. Different methods have been described for explant disinfection, and the main disinfecting solutions used are sodium hypochlorite [19,20] and mercuric chloride [21,22]. In addition, antioxidant additives such as ascorbic acid, citric acid, polyvinylpyrolydon (PVP), anhydrous caffeine and/or sodium diethyldithiocarbonate have been widely used during disinfection in order to reduce explant browning [12,13,19,20].…”
Section: Plant Materials and Disinfectionmentioning
confidence: 99%
“…Othmani et al reported the formation of somatic embryos after 6-7 months of induction in date palm cv. Boufeggous [21]. In date palm cvs.…”
Section: Embryogenic Callus Induction and Somatic Embryo Formationmentioning
confidence: 99%
See 2 more Smart Citations